Fertility, Microbial Biomass and Edaphic Fauna Under Forestry and Agroforestry Systems in the Eastern Amazon - Ruivo, Maria de Lourdes Pinheiro; Junior, Antonio Pereira; Bernardes, Keila Chistina; Amarante, Cristine Bastos; Moura, Quezia Leandro; Macambira, Maria Lucia Jardim (IntechOpen, 2012)
None